2014
DOI: 10.1128/jvi.00704-14
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of HIV-1 cDNA Synthesis by DBR1 Knockdown

Abstract: Previous studies showed that short hairpin RNA (shRNA) knockdown of the RNA lariat debranching enzyme (DBR1) led to a decrease in the production of HIV-1 cDNA. To further characterize this effect, DBR1 shRNA was introduced into GHOST-R5X4 cells, followed by infection at a multiplicity near unity with HIV-1 or an HIV-1-derived vector. DNA and RNA were isolated from whole cells and from cytoplasmic and nuclear fractions at different times postinfection. Inhibition of DBR1 had little or no effect on the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…All structures except the apoenzyme are binuclear with a water/hydroxide bridging the Fe and Zn ions in optimal position to attack the scissile phosphate. The results resolve previous uncertainties regarding Dbr1 active site structure and the newly developed dark-quenched bRNA probe is facilitating the screening of large small molecule libraries for Dbr1 inhibitors that may hold promise as therapeutic agents for neurodegenerative diseases such as ALS (29) and for retroviral infections such as HIV (13,14,17).…”
Section: Significancementioning
confidence: 52%
See 1 more Smart Citation
“…All structures except the apoenzyme are binuclear with a water/hydroxide bridging the Fe and Zn ions in optimal position to attack the scissile phosphate. The results resolve previous uncertainties regarding Dbr1 active site structure and the newly developed dark-quenched bRNA probe is facilitating the screening of large small molecule libraries for Dbr1 inhibitors that may hold promise as therapeutic agents for neurodegenerative diseases such as ALS (29) and for retroviral infections such as HIV (13,14,17).…”
Section: Significancementioning
confidence: 52%
“…gene expression was reported to significantly diminish retroviral replication in cells infected with the HIV (13,14). This observation is consistent with the evolutionarily conserved genetic structures and replication mechanisms of retrotransposons and retroviruses (15,16).…”
Section: Significancementioning
confidence: 99%
“…It has been reported that ssDNA is the predominant cytosolic DNA species during the first 4 h of HIV infection, while dsDNA is found later in the nuclear or perinuclear fractions 37 . Replication of HIV-1 is initiated by reverse transcription of the first ~181 nucleotides of the HIV-1 RNA genome, primed by lysyl-tRNA (tRNA Lys3 ), which generates sstDNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation was that P70 env is found in the perinuclear region of the cytoplasm, which still may allow for interactions between nuclear Zfp111 and P70 env . A second cell fractionation procedure included washing of the nuclei with an ionic/nonionic detergent mixture, to give a perinuclear fraction separate from the rest of the cytoplasm (36,37). Western blot analysis revealed that P70 env was found exclusively in the nuclear fraction along with Zfp111 and not in the perinuclear fraction (Fig.…”
Section: P70mentioning
confidence: 99%